Europe (in theory) - Dainotto, Roberto M. (Duke University Press, 2007)
Europe (in Theory) is an innovative analysis of eighteenth- and nineteenth-century ideas about Europe that continue to inform thinking about culture, politics, and identity today. Drawing on insights from subaltern and postcolonial studies, Roberto M. Dainotto deconstructs imperialism not from the so-called periphery but from within Europe itself. He proposes a genealogy of Eurocentrism that accounts for the way modern theories of Europe have marginalized the continent's own southern region, portraying countries including Greece, Italy, Spain, and Portugal as irrational, corrupt, and clan-based in comparison to the rational, civic-minded nations of northern Europe. Dainotto argues that beginning with Montesquieu's The Spirit of Laws (1748), Europe not only defined itself against an "Oriental" other but also against elements within its own borders: its South.